Teosinte-derived SynCom and precision biofertilization modulate the maize microbiome, enhancing growth, yield, and soil functionality in a Mexican field - Hernández-García, Juan Alfredo; Bernal, Julio S.; Antony-Babu, Sanjay; Villa-Tanaca, Lourdes; Hernández-Rodríguez, César; De-la-Vega-Camarillo, Esaú (Frontiers in Microbiology, 2025)
Modern agriculture faces the challenge of optimizing fertilization practices while maintaining soil resilience and microbial diversity, both critical for sustainable crop production. We evaluated the effects of multiple fertilization strategies on soil microbial communities and plant performance, comparing conventional methods (urea-based and phosphorus fertilizers applied manually or via drone-assisted precision delivery) with biofertilization using a synthetic microbial consortium (SynCom) derived from teosinte-associated microbes. This SynCom consisted of seven bacterial strains: Serratia nematodiphila EDR2, Klebsiella variicola EChLG19, Bacillus thuringiensis EML22, Pantoea agglomerans EMH25, Bacillus thuringiensis EBG39, Serratia marcescens EPLG52, and Bacillus tropicus EPP72. High-throughput sequencing revealed significant shifts in bacterial and fungal communities across treatments. Untreated soils showed limited diversity, dominated by Enterobacteriaceae (>70%). Conventional fertilization gradually reduced Enterobacteriaceae while increasing Pseudomonas and Lysinibacillus populations. Drone-assisted conventional fertilization notably enhanced Acinetobacter and Rhizobiales growth. Biofertilization treatments produced the most pronounced shifts, reducing Enterobacteriaceae below 50% while significantly increasing beneficial taxa like Bacillus, Pantoea, and Serratia. Network analysis demonstrated that microbial interaction complexity increased across treatments, with Bacillus emerging as a keystone species. Drone-assisted biofertilization fostered particularly intricate microbial networks, enhancing synergistic relationships involved in nutrient cycling and biocontrol, though maintaining the stability of these complex interactions requires careful monitoring. Our findings provide key insights into how precision biofertilization with teosinte-derived microbial consortia can sustainably reshape the maize microbiome, improving crop performance and soil resilience.